HLA hart and the making of the new natural law theory - Legarre, Santiago (2017)
This article considers HLA Hart’s influence in the making of John Finnis’s book Natural Law and Natural Rights. In the style of an intellectual biography it traces the history of the interaction between the two Oxford legal philosophers using their correspondence as a starting point. It also delves into Finnis’s years in Africa -a period of his life both crucial for the writing of the book and utterly unknown. It argues that Hart’s role was significant not only insofar as he was behind the idea of the book but also (and this has been little known as of yet) because of the restrained way in which he freely chose to conduct his role as editor despite the extent of the reservations he had regarding Finnis’s work, fully revealed here. Given the importance of Natural Law and Natural Rights for what has been called the ŉew natural law theory’ the article concludes by awarding Hart his due credit in themaking of one of that theory’smain sources of inspiration.